ANALISIS PELAKSANAAN MANAJEMEN PEMUSATAN PENDIDIKAN DAN LATIHAN OLAHRAGA BAGI PUSAT PEMBINAAN LATIHAN MAHASISWA (PPLM) CABANG OLAHRAGA TARUNG DERAJAT KOTA BANDA ACEH - Munzir; Irfandi (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2020)
This study aims to: (1) Determine the organizational structure of the Banda Aceh City Training Center (PPLM) fighting class (2) Know the stages of the process carried out in the recruitment of athletes at the Banda Aceh City Level Training Center for Students Training (3) Knowing management of facilities and infrastructure in supporting the achievements of athletes of the Center for Student Training Development (PPLM) fighting the Banda Aceh City. (4) Knowing the implementation of financial management in the Center for the Training of Student Training (PPLM) fighting the Banda Aceh City degree. (5) Knowing the implementation of the management training of the Tarung College Student Training Development Center (PPLM). The study was conducted at the Central Training Center for Student Training (PPLM) fighting in the city of Banda Aceh. This research uses descriptive qualitative method. The unit of analysis is the Central Training Center for Student Training (PPLM) fighting in the city of Banda Aceh. (1) Organizational Structure of the Center for Training of Students Training (PPLM) fighting in the city of Banda Aceh has been good which already has elements of the organization that continues to strive to facilitate athletes to excel. (2) The process of recruiting athletes has been carried out well because it is very selective and in accordance with the criteria / marking as determined by the standards of the Ministry of Youth and Sports of the Republic of Indonesia (3) The implementation of facilities and infrastructure management is not good, this is because the supporting media for PPLM athlete facilities is not yet complete and only utilize what is there. (4) The implementation of financial management has been carried out well because it is in accordance with their respective portions. (5) The implementation of training management in the Tarung College Student Training Development Center (PPLM) has been going well. Considering the allocation of funds from the APBN and ABPD which is limited to each year, so that management only maximizes in accordance with the allocation of existing funds. Abstrak Penelitian ini bertujuan: (1) Mengetahui struktur organisasi Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh (2) Mengetahui proses tahapan yang dilakukan dalam perekrutan atlet di Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh (3) Mengetahui manajemen sarana dan prasarana dalam mendukung prestasi atlet Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh. (4) Mengetahui pelaksanaan manajemen keuangan di Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh. (5) Mengetahui pelaksanaan manajemen latihan Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh. Penelitian dilaksanakan di Balai Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh. Penelitian ini menggunakan metode diskriptif kualitatif. Unit analisisnya adalah Balai Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh. (1) Struktur Organisasi Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh sudah sudah baik dimana sudah memiliki unsur-unsur organisasi yang terus berupaya memfasilitasi atlet untuk berprestasi. (2) Proses perekrutan atlet sudah dilaksanakan dengan baik karena sangat selektif dan sudah sesuai dengan kriteria/ bencmarking sebagaimana yang ditentukan oleh standar Kemenpora Republik Indonesia (3) Pelaksanaan manajemen sarana dan prasarana kurang baik, hal ini dikarenakan media pendukung fasilitas atlet PPLM belum lengkap sepenuhnya dan hanya memanfaatkan apa yang ada saja. (4) Pelaksanaan manajemen keuangan telah dilaksanakan dengan baik karena sudah sesuai dengan porsinya masing-masing. (5) Pelaksanaan manajemen latihan di Pusat Pembinaan Latihan Mahasiswa (PPLM) tarung derajat Kota Banda Aceh sudah berjalan dengan baik. Mengingat alokasi dana dari APBN dan ABPD yang terbatas pada setiap tahunnya, sehingga pengelolaan hanya memaksimalkan sesuai dengan alokasi dana yang ada. Kata Kunci: Pelaksanaan Manajemen PPLM, Struktur Organisasi, Perekrutan Atlet, Manajemen Sarana Prasarana Manajemen Keuangan Dan Latihan